A global analysis of distribution and endemism within Late Llandovery (Telychian) brachiopods. Issue 3 (3rd July 2019) - Cocks, L. Robin M.; Jiayu, Rong
Abstract : Cocks, L.R.M. & Jiayu, R. 10 July 2019. A global analysis of distribution and endemism within Late Llandovery (Telychian) brachiopods. Alcheringa 43, 406–422. ISSN 0311–5518 The genera of brachiopods of early Silurian (late Llandovery: Telychian) age have been critically reviewed and are listed from the major continental areas: South China, Avalonia-Baltica, Laurentia, Siberia and adjacent areas, and Gondwana (including the adjacent Kazakh terranes, Southwest Tien Shan and Iran). All those continents lay within tropical latitudes, apart from the South American sector of Gondwana, which hosted the Clarkeia Fauna, the earliest constituent of the largely high-latitude Devonian Malvinokaffric Province in the southern hemisphere. Additionally, the then northern (today's southern) part of the Siberian continent, which included parts of Mongolia and North China, was at temperate latitudes in the northern hemisphere so that it hosted the Tuvaella Fauna, which was also dominated by endemic brachiopod genera. Of the 202 genera listed, 50 are endemic to one of the six regions, and a further eight must have lived during Telychian times since they are known from both the underlying Aeronian and the overlying Sheinwoodian. L. Robin M. Cocks [rcocks@nhmacuk ], Department of Earth Sciences, The Natural History Museum, Cromwell Road, London SW7 5BD, UK; Rong Jiayu[jyrong@nigpasaccn ], State Key Laboratory, Nanjing Institute of Geology and Palaeontology, 39 East Beijing Road, Nanjing 210008, PR China.